Biology science learning continuum at the elementary school level based on teachers’ cognitive abilities - Mualimin Mualimin; Bambang Subali; Paidi Paidi (Institute of Advanced Engineering and Science, 2023)
This research aims to develop a biology science learning continuum on the aspects of structure and function at the elementary school (ES) level based on the teachers’ cognitive abilities. This survey research used a reasoned multiple-choice test, having the material aspects of structure and function with the cognitive levels of C1-C2, was developed by listing the key sub-aspects, forum group discussion, item development, expert judgement, and item revision. The test was administered to 240 ES teachers in the Special Region of Yogyakarta, Indonesia, and the results were analyzed through the Quest program. The results reveal that the learning continuum is developed based on the difficulty level of the questions in which item response theory (IRT) shows the respondents’ cognitive ability, the level of cognitive processes from the lower level to the higher ones, the complexity level from the simple to the most complex in each sub-aspect of the structure and function. The sub-aspects with higher cognitive ability scores, lower difficulty index, lower level of cognitive processing, and lower complexity are recommended to at the lower grades. Sub-aspects with lower cognitive ability value, higher difficulty index, higher level of cognitive processing, and higher complexity category are recommended to the higher grades.